Ionospheric Energy Input in Response to Changes in Solar Wind Driving: Statistics From the SuperDARN and AMPERE Campaigns. Issue 3 (8th March 2022) - Billett, D. D.; McWilliams, K. A.; Perry, G. W.; Clausen, L. B. N.; Anderson, B. J.
Abstract: For over a decade, the Super Dual Auroral Radar Network and the Active Magnetosphere and Planetary Electrodynamics Response Experiment have been measuring ionospheric convection and field‐aligned currents in the high‐latitude regions, respectively. Using both, high‐latitude maps of the magnetosphere‐ionosphere energy transfer rate (the Poynting flux) have been generated with a time resolution of 2 min between 2010 and 2017. These data driven Poynting flux (PF) patterns are used in this study to perform a superposed epoch analysis of the northern hemisphere ionospheric response to transitions of the interplanetary magnetic field B z component, upwards of 60° geomagnetic latitude. We discuss the difference in the distribution of PF between the magnetosphere‐ionosphere Dungey cycle "switching on" and "switching off" to solar wind driving, revealing that they are not symmetric temporally or spatially. Plain Language Summary: The Earth's high‐latitude upper atmosphere (the ionosphere, upwards of 100 km in altitude) is consistently bombarded with solar energy that takes the form of electric currents aligned with Earth's magnetic field. The magnetosphere has two generalized states, "open" and "closed." Open is when the Earth and interplanetary magnetic fields (IMFs) connect to each other on the dayside, allowing energy into the atmosphere from the solar wind. Closed is when the fields do not connect (or do not connect simply) and thus not as much energy enters the atmosphere. The aforementioned open or closed states depend on the direction of the IMF, which varies constantly, as well as the history of the field as the magnetosphere takes time to reconfigure. In this study, we utilize nearly 8 years of data to generate average patterns of ionospheric energy input at various intervals before and after the IMF flips in direction. We discuss the spatial and temporal timescales upon which the energy varies in response to the relatively symmetric IMF transitions, finding that they do not result in symmetric changes in the ionospheric energy input patterns. Key Points: The Super Dual Auroral Radar Network and the Active Magnetosphere and Planetary Electrodynamics Response Experiment derived Poynting flux (PF) distributions are used to perform a superposed epoch analysis of interplanetary magnetic field (IMF) B z transitions Changes in the IMF B z component have immediate responses, but continue to evolve for several tens of minutes There is spatial and temporal asymmetry to how the PF morphology responds to opposite B z transitions